Passovia myrsinites a restablished name including Oryctina atrolineata (Loranthaceae) - Caires, Claudenir S.; Gomes-Bezerra, Kadja M.; Proença, Carolyn E. B. (Phytotaxa, 2017)
During our studies of the Brazilian Loranthaceae, an extensive review of names associated to Oryctina and Passovia was carried out. We observed that the leaf architecture and floral structure of Oryctina myrsinites were different from that of other species of the genus. Analyses under Light and Scanning Electron Microscopy showed stellate fiber bundles in the mesophyll, inflorescences formed by sessile triads and laterally excavated filaments. Epicortical roots at the base of the plant were also observed. These characters are diagnostic of Passovia, and we agree with Van Tieghem that Passovia myrsinites is the correct name for this species and have also included Oryctina atrolineata as a new synonym.